Dyeing of cotton fabric with antibacterial properties using direct dye and CTAB - Sama Khanmirzaee; Majid Montazer; Atousa Pashaee (Journal of Natural Fibers, 2020)
Direct dyes still represent an important class of dye for use on cellulose fiber, because of the ease of application and low cost. The present study was aimed at development of microbial resistant cotton using antibacterial agent in dyeing process through exhaustion method. Cetyl tri-methyl ammonium bromide (CTAB), as a cationic antibacterial agent, was used in dyeing of cotton fabric with direct dyes. The antibacterial activities, washing fastness, light fastness, and bending length of the treated fabrics were investigated and the results discussed. To reveal the antibacterial properties of the treated samples, the zone of inhibition was measured for S. aureus and E. coli. Finally, the fabric dyed with 5% NaCl, 5% CTAB, and 2% Direct Blue 86 indicated good antibacterial properties against S. aureus; however, the dyed fabric with 5% NaCl, 1% CTAB, and 2% Direct Blue 86 showed more suitable antibacterial properties against E. coli in compare to other samples. Further, the dyed cotton fabric along with CTAB prevented S. aureus growth more than E. coli.